Further studies on harvestmen (Arachnida: Opiliones) from Iran, with the descriptions of two new species - Snegovaya, Nataly Yu.; Cokendolpher, James C.; Zamani, Alireza (Zootaxa, 2021)
This paper deals with some new material of Iranian harvestmen accumulated during and after 2017. These recent collections yielded 11 species from six families, including five species that had previously been known from Iran, and two families and six species which are established as being new for the fauna of the country. The latter include two newly described species of Phalangiidae, namely Homolophus airyamani spec. nov. (male; Hormozgan Province, southern Iran) and Phalangium martensi spec. nov. (male; Khuzestan Province, southwestern Iran). With the study of new specimens and the recording of previously known material, 28 species from six families of Opiliones are currently known from Iranian territories. The records include one species of Biantidae, one species of Dicranolasmatidae, five species of Nemastomatidae, 19 species of Phalangiidae, and a single species each for Sclerosomatidae and Trogulidae.